Spatio-temporal assessment of gait kinematics in vertical pedestrian-structure interaction. (June 2021) - Gomez, Daniel; Rietdyk, Shirley; Dyke, Shirley J.
Abstract: Pedestrian structures regularly exhibit excessive vibrations when they are dynamically excited by human activities. Traditional modeling approaches neglect, due to the lack of suitable data, the temporal and spatial kinematic changes (such as the step length, step width, pace frequency and horizontal speed) when pedestrians are walking on a vibrating surface in the vertical direction such as slabs, footbridges, or stairs. Although several experimental studies have quantified the variability of human gait, most of these were conducted overground. These procedures do not fully account for the interaction between the pedestrian and an oscillating surface, compromising the comfort in service conditions for their occupants. In this paper, the spatio-temporal gait parameters were measured when six adults were instructed to walk on the beam and on the ground. The kinematic parameters were compared among the individual subjects to evaluate their variability associated with the vertical acceleration influence. Two gait modes were examined in this study, metronomic walk and self-selected pace. The results show that the walking locomotion parameters such as step length, step width, pace frequency, and pedestrian horizontal speed were found to have substantial differences on the ground as compared with the structural vibration under different walking modes. The findings here clearly demonstrate that gait and bridge kinematics interact, and continued research is warranted with larger numbers of participants under a wider range of structural conditions.